Correlation between milk bottle practice and diarrhea on children under five at Puskesmas Umbulharjo 1, Yogyakarta City - Myra Mesnuath Kosapilawan; Delima Citra Dewi Gunawan; Fera Nofiartika (Universitas Respati Yogyakarta, 2019)
Background: Diarrhea is one of the causes of death in children. The incidence of diarrhea in Yogyakarta City in 2014 was still quite high, as many as 917 cases. The use of milk bottles is one of the factors causing diarrhea in children. Milk bottles are susceptible to bacterial contamination due to poorthe use of milk bottles. Objective: To investigate the relationship between the practice of using milk bottles and the incidence of diarrhea in infants in the working area of Umbulharjo 1 Health Center, Yogyakarta City. Methods: The design of this study was cross sectional. The research was conducted in the Umbulharjo Community Health Center work area 1. The research subjects were 138 children aged 0–59 months and using milk bottles. Data were analyzed using Chi Square test to determine the relationship between the practice of using milk bottles and the incidence of diarrhea. Results: The practice of using milk bottles in 89 toddlers (64.5%) was included in the bad category while 49 toddlers (35.5%) were included in the good category. There was a relationship between the practice of using milk bottles with the incidence of diarrhea (p=0.00). Conclusion: The practice of using a good bottle of milk can reduce the risk of diarrhea in infants.